2018
DOI: 10.1097/phm.0000000000000852
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Armeo® Robotic Therapy Versus Conventional Therapy on Upper Limb Function in Children With Hemiplegic Cerebral Palsy

Abstract: Armeo robotic therapy is significantly more effective than conventional therapy in improving the upper limb quality of movement in children with hemiplegic cerebral palsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 53 publications
2
45
0
Order By: Relevance
“…Nonetheless, we also found a study showing that the training with Armeo improved only the MAAULF scale while the QUEST scale remained unchanged, which means improvements in functional gains of the upper limbs and not in the movement characteristics [84]. However, significant improvements in terms of QUEST scale after the training with Armeo has been proven by El-Shamy [85], showing that robotic-assisted therapy is more effective than conventional therapy in promoting functional improvements of upper limbs, suggesting to combine conventional and robotic therapies for the achievement of better rehabilitation gains. In support of this thesis, another study [82] has demonstrated the improvement of functionality of the upper limbs after Armeo Spring training in children with CP and ABI.…”
Section: Robotic Protocols For Upper Limb Rehabilitationsupporting
confidence: 51%
See 2 more Smart Citations
“…Nonetheless, we also found a study showing that the training with Armeo improved only the MAAULF scale while the QUEST scale remained unchanged, which means improvements in functional gains of the upper limbs and not in the movement characteristics [84]. However, significant improvements in terms of QUEST scale after the training with Armeo has been proven by El-Shamy [85], showing that robotic-assisted therapy is more effective than conventional therapy in promoting functional improvements of upper limbs, suggesting to combine conventional and robotic therapies for the achievement of better rehabilitation gains. In support of this thesis, another study [82] has demonstrated the improvement of functionality of the upper limbs after Armeo Spring training in children with CP and ABI.…”
Section: Robotic Protocols For Upper Limb Rehabilitationsupporting
confidence: 51%
“…This device records movement parameters such as resistance, strength, coordination and range of motion and is adjustable according to the patient's condition. We found 7 clinical studies involving this device [81][82][83][84][85][86][87]. It has been used primarily for clinical rehabilitation protocols for children with CP, demonstrating a better quality of upper limb movements due to improvements of QUEST and MAAULF scales at the end of the training [81][82][83].…”
Section: Robotic Protocols For Upper Limb Rehabilitationmentioning
confidence: 99%
See 1 more Smart Citation
“…While our exomuscle is designed for the needs of stroke survivors, other populations might also benefit from similar devices. Gravity supported therapy has shown to improve clinical measures of motor ability in participants with cerebral palsy [50]. Gravity-compensating devices can also provide movement benefits to individuals with muscular dystrophy [51], though most extant examples are mounted to wheelchairs and are not wearable.…”
Section: Discussionmentioning
confidence: 99%
“…They found significant differences in improvement between groups post-treatment in terms of visual motor skills. El-Shamy et al [ 17 ] showed improvements after ARMEO robotic therapy, compared with conventional therapy, in children with hemiplegic CP, with Modified Ashworth Scale and the Quality of Upper Extremity Skills Test. Sajan et al [ 15 ] and Cavalcante Neto et al [ 18 ] concluded that task-specific training affords stronger benefits for general motor skill than Wii-based training.…”
Section: Introductionmentioning
confidence: 99%